The Significance of historical argumentation in process of the Catholic theology revival based on the treatise “De locis theologicis” by Melchior Cano - Rybacki, Rafał (My University, 2018)
W polskiej literaturze przedmiotu nie podjęto dotychczas próby szerszej analizy myśli teologicznej Melchiora Cano. W literaturze obcojęzycznej powstało wiele publikacji, których przedmiotem są poszczególne księgi traktatu. Brak zaś publikacji, która skupiałaby się w szerszym zakresie na związku zachodzącym pomiędzy zawartością traktatu De locis theologicis, a historycznymi okolicznościami, w których znalazła się teologia katolicka na przełomie XV i XVI stulecia. Celem pracy było wykazanie, iż główne znaczenie argumentacji historycznej w dysputach teologicznych polega, według Melchiora Cano, na stworzeniu przestrzeni dla spotkania teologii scholastycznej z renesansowym humanizmem, a co za tym idzie utrzymania naukowego charakteru refleksji teologicznej.

In the Polish literature, due to the topic mentioned above in the paper, they have never taken until nowadays, an attempt of more sophisticated analysis of Melchior Cano’s theological thought. However, numerous publications came into being in foreign language literature. They are devoted to particular books of the treatise. Unfortunately, there is lack of any publication mainly focused on a broader scope of relation between the context of the treatise De locis theologicis, and historical circumstances, where strictly the Catholic theology took place, within XV and XVI centuries. The aim of this paper was to prove that the significance of the historical argumentation in time of theological disputations, due to Melchior Cano, is based on creation of area in order to meet both scholastic theology and the Renaissance humanism. And, in consequence, it should result to remain scientific character of the theological reflexion.
The Significance of historical argumentation in process of the Catholic theology revival based on the treatise “De locis theologicis” by Melchior Cano
Wydział Teologiczny
Keywords: Uniwersytet w Salamance; Sobór Trydencki; Reformacja; argumentacja historyczna; źródła teologii; University in Salamanca; Trident Council; Reformation; historical argumentation; theology sources